Innovation in music future opportunities - Hepworth-Sawyer, Russ; Paterson, Justin; Toulson, Rob (New York : Focal Press, 2021)
Innovation in Music: Future Opportunities brings together cutting-edge research on new innovations in the field of music production, technology, performance and business. Including contributions from a host of well-respected researchers and practitioners, this volume provides crucial coverage on a range of topics from cybersecurity, to accessible music technology, performance techniques and the role of talent shows within music business. Innovation in Music: Future Opportunities is the perfect companion for professionals and researchers alike with an interest in the music industry.
Part I Music production innovation 1. Country Eastern: Contextual and cultural mediation in the recording studio -- two producers, two artists, two cultures 2. Defining and developing a sonic signature in music mixing: A practice-based approach as modern-day studio mentorship 3. Making records within records: Manufacturing phonographic 'otherness' in sample-based Hip Hop production 4. Motormouth: An essay in sonic recontextualization 5. The Individualist: Todd Rundgren's approach to innovation and his 1993 interactive album No World Order 6. Ground control and cloud booths: Using Dante to break geographical barriers to music production7. Music production utilising Internet of Things technologies PART II Music technology innovation 8. development of an Ambisonic Guitar System 9. Retaining pianistic virtuosity in #MIs: Exploring pre-existing gestural nuances for live sound modulation through a comparative study 10. Improvising song writing and composition within a hybrid modular synthesis system 11. Speaker Park: An intersection of loudspeaker design and post-acousmatic composition 12. Sound objects: Exploring procedural audio for theatre 13. Hearing and feeling memories: Connecting image, sound and haptic feedback to create a multisensory experience of photographs 14. Concepts for the design of accessible music technology 15. Security engineering in the arts PART III Performance innovation 16. Transparency and authenticity in the live arena: An exploration of electronic music performance techniques 17. BTS' "Speak Yourself" world tour as an intermedial spectacle of attachment 18. A review of contemporary practices incorporating digital technologies with live classical music 19. Free ensembles and small (chamber) orchestras as innovative drivers of classical music in Germany 20. Transforming musical performance: Activating the audience as digital collaborators 21. The online composer-audience collaboration 22. New instruments as creativity triggers in composer-performer collaboration 23. "My avatar and me": Technology-enhanced mirror in monitoring music performance practice 24. Creative considerations for on-screen visuals in electronic pop music performances PART IV Music business and artist development innovation 25. Towards a quantum theory of musical creativity 26. Observing mood-based patterns and commonalities in music using machine learning algorithms 27. The role of contests and talent shows as part of the artist development process within the music industry 28. Music: Leeds -- supporting a regionalised music sector and scene
OCLC-licensed vendor bibliographic record.
Keywords: Music and technology; Music -- Performance; Sound recordings -- Production and direction; Music trade; MUSIC / Recording & Reproduction; MUSIC / General